State politics and gender diversity in sport governance - Lara Lesch; Shannon Kerwin; Pamela Wicker (Economics of Governance, 2022)
This study investigates the relationship between state politics and sport governance based on an institutional framework and the concept of spillover effects. Specifically, it examines whether spillover effects occur from state parliament and government composition to board gender diversity within sport governing bodies. Organizational-level data from German national and state sport governing bodies were collected ( n 0.167em=0.167em930). They were combined with state-level data on the government composition by gender and political party (parliament, ministers) based on the location of each sport governing body's headquarter. The results show that on average 20.1% of board members in sport governing bodies are women. Regression analyses indicate that the share of parliamentarians from the Social Democrats and the Green party is positively associated with the share of women in sport governance, while the share of Liberals in the parliament is negatively related. The share of women parliamentarians from the Social party and the share of women Conservative ministers are negatively related to women in sport governance. The findings indicate that women representation in sport governance is linked to state politics, suggesting that spillover effects occur from an organizations' political environment.
Keywords: Z28; Z22; R50; L88; 330; Board composition; Institutional framework; Political parties; Sport organization; Women